Knowledge regarding hypertension among the middle-aged group adults of Sunwal, Nawalparasi: a cross-sectional study - Acharya, S; Kandel, B; Regmi , A (Devdaha Medical Journal, 2026)
Introduction: Hypertension has a great impact on cardiovascular disease and death all over the world. Low and middle-income countries, including Nepal, are facing a higher disease burden because of complications arising from uncontrolled hypertension. The patient’s knowledge and perception play an important role in disease management. Due to the limited availability of studies on hypertension knowledge among middle-aged adults, this study aimed to assess their level of knowledge on hypertension. Methods: A descriptive cross-sectional study was conducted among 150 respondents using convenience sampling. Data were collected using a structured and semi-structured questionnaire administered via interviews. SPSS version 20 was used to enter and analyze data. Results: Among 150 respondents, most (78%) of the respondents were Hindu, and the least (8.66%) were Buddhist. The majority (38%) of the respondents belong to a nuclear family. The majority (60%) had primary education. Most (60%) of the respondents’ monthly income was Rs. 5000-10,000, while the least (16%) was Rs. 1000-5000. Most of the respondents were involved in business (38%), while laborers (9%) were the least. Out of 150 respondents, 30% had inadequate knowledge, and 70% had adequate knowledge regarding hypertension. Education and occupation were significantly associated with knowledge (p=0.03). Conclusion: A majority of the middle-aged adults had adequate knowledge about hypertension. There was a significant relationship between levels of knowledge and socio- demographic variables such as occupation and education.